Whole-genome sequencing of the rare Salmonella enterica serovar Anfo isolated from food handlers. Issue 3 (30th January 2019) - Octavia, Sophie; Zulaina, Siti; Seet, Swee Kai; Tien, Wee Siong; Thu, Minn; Ooi, Peng Lim; Cui, Lin; Lin, Raymond T. P.
Abstract : Field investigations were conducted after a small cluster of food poisoning involving six cases was reported. While no stool samples were available from the cases for microbiological testing, Salmonella species was found to be present in the stools of food handlers with gastroenteritis symptoms. Four Salmonella isolates recovered from the food handlers were retrospectively investigated at the genome level using whole-genome sequencing (WGS). WGS showed that S . Anfo (antigenic formulae 39:y:1, 2), a rarely isolated serovar, caused infections in the food handlers. S . Anfo analysed in this study contained virulence factors required for causing disease. They did not contain any antibiotic resistance genes or plasmid. The epidemiologically related isolates differed to each other by a maximum of one single nucleotide polymorphism. WGS was useful in identifying rare Salmonella serovars and it is potentially more cost-effective than traditional serotyping methods. It can also confidently group epidemiologically related isolates belonging to S . Anfo.